Models and Methodologies for Predicting Financial Results in Enterprise Management - M. U., Mukhammadjonov (Journal of Innovation in Education and Social Research, 2025)
In the context of increasing market uncertainty, financial forecasting has become a critical component of enterprise management. Accurate forecasting of financial results enables companies to evaluate risks, allocate resources efficiently, and design sustainable development strategies. This article examines the theoretical foundations, models, and methodologies of financial forecasting, emphasizing their role in enterprise management. Traditional approaches, such as ratio analysis, balance sheet methods, and discounted cash flow models, are discussed alongside modern optimization and econometric methods. Furthermore, a comparative analysis of forecasting models is conducted to highlight their advantages, limitations, and areas of application. The findings underline that an integrated use of different methodologies enhances both the accuracy and reliability of financial predictions, which, in turn, contributes to improved strategic decision-making.